(untitled) (Advances in Applied Mathematics and Mechanics, 2023)
The main theme of the current article is to investigate the heat transfer in the pulsatile flow of an electrically conducting viscous fluid in a constricted channel under the effect of the magnetic field and thermal radiation. The unsteady governing equations simplified for low conducting fluids are solved numerically by finite difference method using stream-vorticity function formulation. The influence of the flow parameters such as the Hartmann number (magnetic parameter), Strouhal number (flow pulsation parameter), Prandtl number, and radiation parameter is studied on the relevant flow profiles. The influence of different emerging parameters on the skin friction coefficient and Nusselt number are examined, as well. In general, the profiles are observed to exhibit a relatively more regular pattern upstream of the construction than that downstream of the constriction.